Synthesis and Pharmacological Evaluation of New (Indol-3-yl)Alkylamides and Alkylamines Acting as Potential Serotonin Uptake Inhibitors - Fouchard, Fabienne; Menciu, Cecilia; Duflos, Muriel; Baut, Guillaume Le; Lambrey, Bernard; Mourgues, Marie; Perrissoud, Daniel (Arzneimittelforschung, 1999)
A series of new indolylalkylamides 3-18 and alkylamines 19-26 has been prepared in the search of novel 5-hydroxytryptamine (5-HT) uptake inhibitors. Synthesis of N-2,3 or 4-pyridinyl-(indol-3-yl) acetamides and propionamides 3-10 was achieved starting from the corresponding Ph3P/BrCC13 or DCC-activated acids. Reduction of the pyridine nucleus led to the N-piperidinylalkylamides 15-18 via the tetrahydropyridinyl derivatives 11-14, and LiAlH4 reduction afforded the desired amines 19-26. The affinity of these compounds for 5-HT and also dopamine (DA) and noradrenaline (NA) uptake sites was measured. Among the 16 studied amides only N-(methylpiperidin-3-yl)-(indol-3-yl) propionamide 16 exhibited a moderate 5-HT uptake inhibitory effect: 38% at 10 µmol/l. In contrast, the N-pyridinyl-(indol-3-yl)alkylamines 19-26 exerted high inhibition at this concentration and two of them, 23 and 24, remained very efficient at 0.1 µmol/l. Optimal activity was observed in the 4- pyridinyl subseries and was compatible with variation (n = 1, 2) of the length of the interspacing alkylamino chain. Although 23 and 24 were about 17-fold less active than indalpine as 5-HT uptake inhibitors, they demonstrated, like indalpine, excellent selectivity for the 5-HT uptake site versus the DA uptake site. Both amines inhibited tetrabenazine-induced hypothermia and potentiated 5-HTP- induced behavioural effects in mice. The absence of 3,4-dioxyphenylalanine (dopa)-induced behavioural effects with compound 24 suggests possible antidepressant activity through selective inhibition of central neuronal serotonin uptake and/or increased monoamine release.
Keywords: 5-Hydroxytryptamine, uptake inhibitors; N-Piperidinyl-(indol-3-yl)alkylamides; N-Pyridinyl-(indol-3-yl)acetamides; N-Pyridinyl-(indol-3-yl)ethylamines and propylamines; Tetrahydropyridinyl-(indol-3-yl)alkylamides